2017
DOI: 10.21037/jtd.2017.07.06
|View full text |Cite
|
Sign up to set email alerts
|

Statins may be beneficial for patients with pulmonary hypertension secondary to lung diseases

Abstract: Background: Previous animal studies and clinical trials report inconsistent findings regarding the role of statins in pulmonary hypertension (PH). Systematic reviews have shown no use of statins on pulmonary arterial hypertension (PAH). This is the first meta-analysis of randomized controlled trials (RCTs) determining the clinical impacts of statin therapy on patients with PH secondary to lung diseases.Methods: Electronic databases and manual bibliographical searches were conducted. Eligible studies include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…However, it didn’t study COPD death. Zhang et al found [17] that statins therapy was associated with reduced pH which including six studies, the SMD (95% CI) was − 0.70 (− 0.99, − 0.41). PH is a serious and progressive vascular disease, which is yet incurable and generally results in heart failure and death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it didn’t study COPD death. Zhang et al found [17] that statins therapy was associated with reduced pH which including six studies, the SMD (95% CI) was − 0.70 (− 0.99, − 0.41). PH is a serious and progressive vascular disease, which is yet incurable and generally results in heart failure and death.…”
Section: Discussionmentioning
confidence: 99%
“…What needs to be emphasized is that anti-inflammatory actions modulate the immune system and reduce inflammatory markers such as CRP and IL-6 are slowly being discovered [11, 14]. Systematic reviews prior to 2017 have been suggested that statins are associated with a beneficial role in treatment of COPD [1517], which including reduce all-cause mortality, cause-specific mortality and PH. Li et al research which including twenty studies with a total of 303,981 patients found [16] statins reduced all-cause mortality and COPD exacerbation, but not to hospitalization.…”
Section: Backgroundsmentioning
confidence: 99%
See 2 more Smart Citations
“…potwierdzono, że statyny zmniejszają częstość zaostrzeń, częstość hospitalizacji i antybiotykoterapii u pacjentów z POCH, ponadto przyjmowanie statyn wiązało się ze znacznie mniejszą liczbą hospitalizacji w oddziale ratunkowym [29]. W innym badaniu wskazuje się na korzystne działanie statyn u pacjentów z nadciśnieniem płucnym powstałym w przebiegu przewlekłych chorób płuc, w tym POCH, a terapia statynami wiązała się ze zwiększeniem wydajności wysiłkowej i zmniejszeniem ciśnienia w tętnicy płucnej [31]. Opublikowane wyniki badań retrospektywnych stoją w sprzeczności z opublikowanym w 2014 r.…”
Section: Przewlekła Obturacyjna Choroba Płucunclassified